Relación entre la onicofagia y patologías bucales en pacientes pediátricos. revisión bibliográfica - Castillo Cantos, Johset Salomón (2025)
Onychophagia is an increasingly frequent and common childhood-onset habit that can have negative consequences on oral health. Despite its prevalence and potential adverse effects, there is a lack of clear understanding of the relationship between onychophagia and oral pathologies. Objective: To identify the relationship between onychophagia and oral pathologies in pediatric patients. Materials and Methods: A thorough search and analysis of scientific articles in various specialized databases, such as PubMed, ScienceDirect and LILACS, was carried out. A compilation of information supported by search strings was also carried out, making use of Boolean operators to optimize the identification of relevant data. Results: Initially, a set of 63 scientific articles was collected, of which by means of PRISMA parameters, 9 relevant articles were considered after a selection process based on inclusion and exclusion criteria. Conclusions: There is a relationship between onychophagia and oral pathologies in pediatric patients, for this reason previous studies highlight the transcendence of detecting and addressing onychophagia in a timely manner due to its possible effects on functional and anatomical development. It is important to identify the factors that can trigger onychophagia to avoid long-term complications such as dental malformations, anterior open bite, increased overjet, posterior crossbite, deep palate.